Learn computer science on pathfinder! - A VR game for students to learn computer science module - Lim, Andre You Qiang (Nanyang Technological University, 2024)
With gamification and advancements in technology, it brings novel and unique ways to enhance the learning experiences of students. One such example is the introduction of Virtual Reality (VR) in gamified education. VR brings many benefits such as engagement and immersion for players, thus keeping the user’s attention. Such qualities are extremely advantageous in the field of education and helps improve the learning experience. In this final year project, a VR escape room game that aims to teach Computer Science concepts was developed. Players explore the virtual environment, solving puzzles related to depth first search (DFS). Furthermore, the responses of players were collected and evaluated. A total of 12 responses were collected, half of which had not learnt DFS. Of the 12 players, there were nine year 1 students, one year 2 student, and two graduates. The results of the responses were generally positive, with more than 75% of players indicating that the game was engaging, immersive and helped enhance their learning experience. Furthermore, all players agreed that the game was successful in teaching them the concepts of DFS.